2019
DOI: 10.3390/v11010068
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Flavivirus Host Dependency Factors through a Genome-Wide Gain-of-Function Screen

Abstract: Flaviviruses, such as dengue (DENV), West Nile (WNV), yellow fever (YFV) and Zika (ZIKV) viruses, are mosquito-borne pathogens that present a major risk to global public health. To identify host factors that promote flavivirus replication, we performed a genome-wide gain-of-function cDNA screen for human genes that enhance the replication of flavivirus reporter particles in human cells. The screen recovered seventeen potential host proteins that promote viral replication, including the previously known dolichy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…1A). Numerous research groups have demonstrated that these RPs may be utilized by diverse viruses for efficient viral infection (25,30,(37)(38)(39)(40)(41)(42)(43)(44). Notably, the candidate protein RPL13, a member of the L13E family, is conserved in a wide range of species, including plants, yeast, and animals (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…1A). Numerous research groups have demonstrated that these RPs may be utilized by diverse viruses for efficient viral infection (25,30,(37)(38)(39)(40)(41)(42)(43)(44). Notably, the candidate protein RPL13, a member of the L13E family, is conserved in a wide range of species, including plants, yeast, and animals (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…Genome-scale CRISPR and siRNA screens and proteomic analysis of cellular proteins associated with ZIKV or DENV proteins identified numerous host factors required for viral replication (38)(39)(40)(41)(44)(45)(46). A large part of these host dependency factors are localized in the ER.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA was subsequently amplified using DreamTaq DNA polymerase (ThermoFisher Scientific). The 20-µL reaction volume contained 1x of reaction mix and 10 µM of primers (forward: 5′-GCGTAAGGCTGGAAAGAGTG-3′; reverse: 5′-CTTCCTCCCTTCATCCACAA-3′) 40 . The thermocycling program was 2 min at 95 °C, 35 cycles of 30 sec at 95 °C, 30 sec at 60 °C, and 30 sec at 72 °C with a final extension step of 7 min at 72 °C.…”
Section: Methodsmentioning
confidence: 99%